To simplify two or more numbers which are having same or different signs, we follow the steps given below.
If two numbers are having same signs, + and + (or) - and -, we have to add them and put greater number's sign for the answer.
If two numbers are having different signs, + and - (or) - and +, we have to subtract them and put greater number's sign for the answer.
Simplify the following :
Problem 1 :
(-12) + (-1)
Solution :
(-12) + (-1)
Since these are having same signs, we add them and put greater number's sign for the answer.
= -12 – 1
= -13
Problem 2 :
(-9) + 11
Solution :
Since the given two numbers are having different signs, subtract the smaller from larger and use the sign of the larger number to the answer.
(-9) + 11 = 2
Problem 3 :
(-4) + (-8) + 11
Solution :
(-4) + (-8) + 11
Simplify the numbers which are same signs first.
= -4 – 8 + 11
= -12 + 11
Now we have different signs, so we subtract them and put greater number's sign for the answer.
= -1
Problem 4 :
3 + (-11) + 8
Solution :
= 3 + (-11) + 8
Combine the numbers which are having same signs first.
= 3 + 8 - 11
= 11 - 11
= 0
Problem 5 :
(-4) + 6 + (-3)
Solution :
(-4) + 6 + (-3)
= -4 + 6 – 3
= 2 – 3
= -1
Problem 6 :
1 + (-4) + 10
Solution :
1 + (-4) + 10
First combine the terms which are having same signs.
= 1 + 10 - 4
= 11 - 4
Since they are having different signs, subtract 4 from 11 and put positive sign for the answer.
= 7
Problem 7 :
(-5) + (-5) + 1
Solution :
(-5) + (-5) + 1
First combine the terms which are having same signs.
= -5 - 5 + 1
= -10 + 1
Since they are having different signs, subtract 1 from 10 and put negative sign for the answer.
= -9
Problem 8 :
1 + (-3) + 11
Solution :
1 + (-3) + 11
First combine the terms which are having same signs.
= 1 + 11 - 3
= 12 - 3
Since they are having different signs, subtract 3 from 12 and put positive sign for the answer.
= 9
Problem 9 :
(-9) + 4 + 7
Solution :
First combine the terms which are having same signs.
= (-9) + 4 + 7
= -9 + 11
Since they are having different signs, subtract 3 from 12 and put positive sign for the answer.
= 2
Problem 10 :
(-12) + 4 + 8
Solution :
(-12) + 4 + 8
= -12 + 12
= 0
Problem 11 :
3 + (-10) + 6
Solution :
= 3 + (-10) + 6
= 9 - 10
= -1
Problem 12 :
(-3) + 3 + 12
Solution :
= (-3) + 3 + 12
= -3 + 15
= 12
Problem 13 :
(-4) – (-8) - 2
Solution :
(-4) – (-8) - 2
= -4 + 8 – 2
= -4 - 2 + 8
= -6 + 8
= 2
Problem 14 :
(-2) – (-1) - (-7)
Solution :
= (-2) – (-1) - (-7)
= -2 + 1 + 7
= -2 + 8
= 6
Problem 15 :
2 – (-5) - 3
Solution :
= 2 – (-5) - 3
= 2 + 5 – 3
= 7 – 3
= 4
Problem 16 :
(-7) – (-7) - 4
Solution :
= (-7) – (-7) – 4
= -7 + 7 – 4
= -7 - 4 + 7
= -11 + 7
= -4
Problem 17 :
(-6) – 4 – (-4)
Solution :
= (-6) – 4 – (-4)
= -6 – 4 + 4
= -10 + 4
= -6
Problem 18 :
(-8) – (-8) - 5
Solution :
= (-8) – (-8) - 5
= -8 + 8 – 5
= -8 - 5 + 8
= -13 + 8
= -5
Problem 19 :
(-5) – 6 - (-6)
Solution :
= (-5) – 6 - (-6)
= -5 – 6 + 6
= -11 + 6
= -5
Problem 20 :
6 – (-3) - 1
Solution :
= 6 – (-3) - 1
= 6 + 3 – 1
= 9 – 1
= 8
Sep 22, 23 08:41 AM
Sep 22, 23 06:13 AM
Sep 22, 23 06:09 AM